Laterally‐coupled distributed feedback laser with first‐order gratings by interference lithography. Issue 12 (1st June 2013) - Li, Jingsi; Cheng, Julian
Abstract : The first laterally‐coupled distributed feedback (DFB) laser with first‐order sidewall gratings fabricated by optical interference lithography is experimentally demonstrated. The gratings were first etched into a dielectric mask on the planar top surface of an InP/AlGaInAs laser epiwafer, and then transferred to both sidewalls of a 2 µm deep ridge‐waveguide structure using a novel self‐aligned process. DFB ridge‐waveguide lasers with a cavity length of 650 µm and width of 2.6 µm (with 300 nm gratings on both sidewalls) achieved single longitudinal mode continuous‐wave operation, with a sidemode suppression ratio of 37 dB. The threshold current density is 1.7 kA/cm 2 at room temperature, and the slope efficiency is 0.14 mW/mA per facet (uncoated).